After-tax term structures of real interest rates: Inferences from the UK linked and non-linked gilt markets - Aziz, Andrew R.; Prisman, Eliezer Z. (Journal of Banking & Finance, 2000)
This study estimates the after-tax term structure of real interest rates using the prices of UK linked and non-linked gilts over the period from 25 January 1986 until 25 October 1993. The impact of differential taxation and the existence of “noise” in observed market prices is found to produce a significant impact on the parameter estimation of term structure models when compared to methods, such as Brown and Schaefer (Brown, R., Schaefer, S., 1994. Journal of Financial Economics 35, 1–42), that did not. Two major observations can be made regarding the estimates for spot real interest rates. Firstly, the volatility of the short-term rate is much lower than that found by Brown and Schaefer (1994) which provides a better fit with the predictions of the CIR single factor model for interest rates. Secondly, consistent with Rumsey (Rumsey, J., 1993. An impact of the assumptions about taxes on the estimation of the properties of interest rates. Working Paper), there appears to be some evidence to suggest that single factor interest rate models produce a better fit to interest rates on an after-tax basis than on a before tax basis.